Burdigalian-Langhian foraminifera of the northwest High Zagros Thrust Belt, southwest Iran - Roozpeykar, Asghar; Moghaddam, Iraj Maghfouri; Yaazdi, Mehdi; Yousefi, Bijan (Geologos, 2021)
The foraminiferal contents of the lower–middle Miocene succession exposed in three sections in north Nur Abad on the northwestern side of the High Zagros Thrust Belt were studied. Assemblages of larger foraminifera from these sections can be referred to Zone SBZ 25 (and the Miogypsina globulus and Miogypsina intermedia subzones), which correlates with the Burdigalian Stage. For the first time, planktonic foraminifera documented from the Nur Abad area document Lang-hian deposits in the High Zagros, the upper 20 metres of the upper Sayl Cheshmeh section being characterised by the occurrence of planktonic foraminifera such as Globigerina concinna (Reuss), Globigerina diplostoma (Reuss), Globigerinoides obliquus (Bolli), Orbulina bilobata (d’Orbigny) and O.universa (d’Orbigny). This association characterises the Orbulina suturalis Interval Zone.